2020
DOI: 10.1002/mus.26885
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the cutoff value for increment increases the sensitivity for the diagnosis of Lambert‐Eaton myasthenic syndrome

Abstract: Background Increment of compound muscle action potential amplitude is a diagnostic hallmark of Lambert‐Eaton myasthenic syndrome (LEMS). Making a diagnosis can be challenging, therefore, a proper cutoff for abnormal increment is highly relevant for improved recognition of this rare disease. Methods We determined the sensitivity and specificity of 60% and 100% cutoff values in all consecutive patients who underwent increment testing in our hospital from 1999 to 2016. Results We included 156 patients, 63 with LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…7 Our study showed that a CMAP increase of ≥60% provided a sensitivity of 96% and a specificity of 98% in diagnosing LEMS. 13 Lipka et al’s 19 study confirmed this finding.…”
Section: Lambert-eaton Myasthenic Syndromementioning
confidence: 71%
“…7 Our study showed that a CMAP increase of ≥60% provided a sensitivity of 96% and a specificity of 98% in diagnosing LEMS. 13 Lipka et al’s 19 study confirmed this finding.…”
Section: Lambert-eaton Myasthenic Syndromementioning
confidence: 71%
“…Patients with LEMS experience peak muscle weakness in the morning that progressively improves through the day with exercise, whereas the opposite is true for patients with MG (9). This is reflected by EMG findings that show potentiation of compound muscle action potential (CMAP) with exercise or high frequency (10–50 Hz) repetitive nerve stimulation (RNS) in LEMS, whereas the opposite finding is seen with MG. A increase in CMAP amplitude of 60%–100% after RNS or isometric exercise is strongly suggestive of presynaptic neuromuscular junction disorder (10).…”
Section: Discussionmentioning
confidence: 99%
“…For assessment of facilitation, ≥ 100% increment in the CMAP at HRS or after 10 s exercise test is pathognomonic of LEMS [2]. Recent studies showed that ≥ 60% increment is sufficient for the diagnosis of LEMS with 97% diagnostic sensitivity and 98% diagnostic specificity [10,11].…”
Section: Lambert-eaton Myasthenic Syndromementioning
confidence: 99%
“…Recent studies showed that ! 60% increment is sufficient for the diagnosis of LEMS with 97% diagnostic sensitivity and 98% diagnostic specificity [10,11].…”
Section: Electrodiagnostic and Voltage Gated Calcium Channel Antibody...mentioning
confidence: 99%